2017
DOI: 10.1021/acs.analchem.7b01349
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Immunochips for High-Accuracy Detection of AFP-L3% Based on Surface-Enhanced Raman Scattering: Implications for Early Liver Cancer Diagnosis

Abstract: α-Fetoprotein (AFP) is an important tumor biomarker. In particular, the overexpression of AFP-L3 is associated with hepatocellular carcinoma (HCC). Accordingly, several hospitals have begun to employ the ratio of AFP-L3 to the total AFP level (AFP-L3%) as new diagnostic evidence for HCC owing to its high diagnostic accuracy. However, current methods of detection for AFP and AFP-L3 are time-consuming, require multiple samples, and lack in sensitivity and specificity. Herein, we present a novel concept for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 37 publications
1
70
0
Order By: Relevance
“…Notably, the present study revealed a negative association between serum AFP and IL-37 of cancer tissues, but not in PT. AFP usually increases with the deterioration of hepatocellular carcinogenesis and is a relatively specific clinical index for the diagnosis of primary liver cancer, but the specificity and sensitivity of diagnosis are relatively low (26). Some researchers have tried to combine AFP detection with some interleukin detection for the diagnosis and prognosis of liver cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the present study revealed a negative association between serum AFP and IL-37 of cancer tissues, but not in PT. AFP usually increases with the deterioration of hepatocellular carcinogenesis and is a relatively specific clinical index for the diagnosis of primary liver cancer, but the specificity and sensitivity of diagnosis are relatively low (26). Some researchers have tried to combine AFP detection with some interleukin detection for the diagnosis and prognosis of liver cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…Siripongsakun et al and Zhang et al suggested that the postoperative measurement of AFP in these HCC populations may not be helpful and should be omitted because of its poor sensitivity. Although several markers may be used in the prediction and diagnosis of HCC, including AFP‐L3, glypican‐3, cyclase‐associated protein 2 (CAP2), AFP‐mRNA, and the half‐life of serum AFP, there are many limitations to the use of these markers in clinical practice . Many staging systems have been used for the classification and prognostication of HCC, including the TNM system, Okuda score, Japan Integrated Staging score, CLIP score, and BCLC stage .…”
Section: Introductionmentioning
confidence: 99%
“…Although several markers may be used in the prediction and diagnosis of HCC, including AFP-L3, glypican-3, cyclase-associated protein 2 (CAP2), AFP-mRNA, and the half-life of serum AFP, there are many limitations to the use of these markers in clinical practice. [11][12][13][14] Many staging systems have been used for the classification and prognostication of HCC, including the TNM system, Okuda score, Japan Integrated Staging score, CLIP score, and BCLC stage. [15][16][17][18] Nonetheless, these classification criteria vary considerably, present controversial results, and are divided into different groups with varying prognostic results and therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplexed detection of low concentration (~5 pM) of AFP and glypican‐3 biomarkers in serum samples of HCC patients have been reported using this method . Quantitative assessment of AFP‐L3 for early diagnosis of HCC has been demonstrated by incorporating sandwich complex and shift immunoassay . Scheme for this study is shown in Figure d.…”
Section: In Vitro Detection Of Biomarkers With Sers For Cancer Diagnomentioning
confidence: 99%